Assessment of historical and future changes in temperature indices for winegrape suitability in Hungarian wine regions (1971–2100) - Lakatos, László; Nagy, Richárd (Frontiers in Plant Science, 2025)
Climate change is significantly impacting our agricultural crops and their cultivation areas, which are expected to change considerably by the end of the century. Temperature conditions decisively influence the safe suitability of grapes in a given location. To address these changes, we analysed the temporal changes of four temperature indicators: Average Growing Season Temperature (AGST), Growing Degree Days (GDD or Winkler index (GDD-WI), Huglin index (HI), and Biologically Effective Degree Days (BEDD) across 22 Hungarian wine regions from 1971 to 2100. The analysis was based on data from 14 climate models under RCP 4.5 and RCP 8.5 scenarios. To investigate the future suitability of wine grapes, we introduced the dynamic suitability function, which allowed us to analyse the suitability of the average temperature during the growing season for 21 wine grape varieties from 2031 to 2100 in decadal increments. Additionally, a temperature impact function was introduced to characterise the suitability of 21 wine grape varieties with values ranging from 0 to 1, based on the average temperature during the growing season. The results confirmed that the frequency of temperature indices used in grape cultivation will shift distinctly towards warmer climate classes in the future. The increasingly warmer climate presents certain advantages but also has growing cultivation risks. In the most optimistic scenario, the average temperature during the growing season may decrease by 0.8°C over the next seven decades. However, in the most pessimistic model, the change expected by the end of the century exceeds a 4.0°C increase. For wine grape varieties with lower heat requirements, suitability under the pessimistic RCP 8.5 emission scenario is projected to decrease by 29% by the end of the century. Conversely, under the optimistic scenarios, the decline in suitability values is only between 3-4%. For grape varieties with higher heat requirements, a 10% decrease in suitability is expected under the RCP 8.5 scenario. In contrast, the RCP 4.5 scenario suggests that suitability could improve by 1-2% by the end of the century. These findings contribute to a better understanding of the impacts and consequences of climate change and offer insights on how to prepare for these challenges in the viticulture sector.